Pengaruh Karakteristik Pemerintah Daerah dan Temuan Audit BPK Terhadap Kinerja Keuangan Pemerintah Daerah Kab/Kota pada Provinsi Sumatera Utara - Agintha, Nabilla Dwi (Jurnal Riset AKuntansi dan Bisnis, 2024)
Performance is the Output/Result of the Program/Activity to be or has been achieved in connection with the use of budget with measurable quantity and quality. Financial Performance is determined by many factors. The purpose of the research was to obtain empirical evidence of the Influence of Local Government Characteristics proxyed by Local Government Size, Regional Wealth Level, Level of Dependence on Central and Capital Expenditure and Bpk Audit Findings on Financial Performance. The type of research used is quantitative research. This research was conducted on the District / City Government in North Sumatra Province. The population in this study was 33 populations with a period of 4 years of research, so the number of observations in this study was 132 data. The data analysis method used in this study is Data Panel Regression Analysis conducted with the help of Eview software.The result of the coefficient of determination was 0.432173 or (43.21%) meaning that independent variables can explain Financial Performance, the remaining 56.79% is explained by other variables that are not included in the research model. The F test results show that the Size of Local Government, Regional Wealth Level, Level of Dependence on The Center, Capital Expenditure and Bpk Audit Findings have a joint effect on Financial Performance. The results of the T test showed that the Size of Local Government, The Level of Dependence on the Center, and Capital Expenditure had a positive and significant effect on alpha five percent on Financial Performance while the Regional Wealth Level and bpk audit findings did not have a significant influence on financial performance.